2013
DOI: 10.1016/j.bbamcr.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor induces collagen I expression in human lung fibroblasts through the Rac1/MLK3/JNK/AP-1 pathway

Abstract: Connective tissue growth factor (CTGF) plays an important role in lung fibrosis. In this study, we investigated the role of Rac1, mixed-lineage kinase 3 (MLK3), c-Jun N-terminal kinase (JNK), and activator protein-1 (AP-1) in CTGF-induced collagen I expression in human lung fibroblasts. CTGF caused concentration- and time-dependent increases in collagen I expression. CTGF-induced collagen I expression was inhibited by the dominant negative mutant (DN) of Rac1 (RacN17), MLK3DN, MLK3 inhibitor (K252a), JNK1DN, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…In yet another study, CTGF was found to increase phosphorylation of five phosphoproteins including SAPK/JNK58. Retrospectively, there are a number of reports which indicate the regulation of CTGF by SAPK/JNK signalling wherein CTGF has been shown to produce its effects in the presence of active SAPK/JNK pathway5960.…”
Section: Discussionmentioning
confidence: 98%
“…In yet another study, CTGF was found to increase phosphorylation of five phosphoproteins including SAPK/JNK58. Retrospectively, there are a number of reports which indicate the regulation of CTGF by SAPK/JNK signalling wherein CTGF has been shown to produce its effects in the presence of active SAPK/JNK pathway5960.…”
Section: Discussionmentioning
confidence: 98%
“…46 As a result, connective tissue growth factor (CTGF), a known downstream mediator of TGF-β, induces proliferation of myofibroblasts and expression of collagen types I and III. 47 Sisco et al 48 reported that inhibition of CTGF activity limited hypertrophic scarring via the suppression of myofibroblasts, collagen and tissue inhibitor of metalloproteinase (TIMP)-1 expression. The repression of apoptosis, mechanobiology, angiogenesis, and inflammatory responses can also contribute to a reduction in scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms involving co-regulation with TGF-β and cooperation with autocrine TGF-β have been reported, but it is possible that TGF-β-independent mechanisms, such as mitogen-activated protein kinase- and AP-1-mediated collagen transcription, exist. 4 Dissection of these signaling intricacies involving AP-1 is made difficult, however, by imponderables such as codependency of AP-1 and SMADs in classical TGF-β signaling.…”
mentioning
confidence: 99%